Peran ASEAN dalam Meningkatkan Keamanan Kawasan dan Stabilitas Ekonomi melalui Kerjasama Pertahanan - Thea Diva; Suwito Suwito; Sri Yanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The role of ASEAN in strengthening regional security and economic stability through defense cooperation is becoming increasingly pivotal in response to evolving global geopolitical and economic challenges. This study employs a qualitative methodology, specifically a literature study approach, to analyze ASEAN's mechanisms for fostering defense collaboration and their impact on the region's stability. Central to this analysis are key initiatives such as the ASEAN Defence Ministers’ Meeting (ADMM) and ADMM-Plus, which have enhanced regional security through joint military exercises, intelligence sharing, and maritime security efforts. These initiatives have been instrumental in mitigating tensions, particularly in contested areas like the South China Sea, safeguarding critical trade routes, and promoting economic resilience. The findings indicate that ASEAN's defense cooperation directly supports economic stability by fostering a secure environment that encourages foreign investment, intra-ASEAN trade, and infrastructure development. However, the study identifies significant challenges, including disparities in member states' defense capabilities, limited inter-state trust, and a tendency to prioritize arms modernization over institutional collaboration. Moreover, ASEAN faces the growing need to address non-traditional security threats, such as cybercrime and terrorism, which require adaptive strategies and enhanced cooperation. The research concludes that while ASEAN’s defense collaboration bolsters military preparedness, it also significantly contributes to political stability and economic growth in Southeast Asia. To sustain and amplify these benefits, ASEAN must address existing challenges through measures such as enhancing transparency, fostering trust among member states, and investing in capacity-building initiatives.